The Intergenerational Impact of the African Orphans Crisis : A Cohort Study from an HIV/AIDS Affected Area - Beegle, K.; De Weerdt, J.; Dercon, S. (2012)
BACKGROUND: In sub-Saharan Africa, the prevalence of orphanhood among children has been greatly exacerbated by the HIV/AIDS pandemic. If orphanhood harms a child's development and these effects perpetuate into adult life, then the African orphan crisis could seriously jeopardize the continent's future generations. Whether or not there exists an adverse, causal and intergenerational effect of HIV/AIDS on development is of crucial importance for setting medical priorities. This study is the first to empirically investigate the impact of orphanhood on health and schooling using long-term longitudinal data following children into adulthood. METHODS: We examined a cohort of 718 children interviewed in the early 1990s and again in 2004. Detailed survey questionnaires and anthropometric measurements were administered at baseline and during a follow-up survey. Final attained height and education (at adulthood) between children who lost a parent before the age of 15 and those who did not were compared. RESULTS: On average, children who lose their mother before the age of 15 suffer a deficit of around 2 cm in final attained height (mean 1.96; 95% CI 0.06-3.77) and 1 year of final attained schooling (mean 1.01; 95% CI 0.39-1.81). This effect is permanent and the hypothesis that it is causal cannot be rejected by our study. Although father's death is a predictor of lower height and schooling as well, we reject the hypothesis of a causal link. CONCLUSIONS: The African orphan crisis, exacerbated by the HIV/AIDS epidemic will have important negative intergenerational effects.